Observations of DNA transfer within an operational Forensic Biology Laboratory. (July 2016) - Taylor, Duncan; Abarno, Damien; Rowe, Emily; Rask-Nielsen, Lauren
Abstract: Advances in technology to both generate and interpret DNA profiles has seen the expansion of the ability to provide opinions about results obtained from very low levels of starting biological material. The response in court has been to question the mode by which the DNA came to be on an item, rather than questioning its presence. This brings into play a number of real-world aspects such as transfer of biological material, persistence of biological material on items, shedding ability of individuals, just to name a few. There have been a number of studies that investigate different aspects relating the mode of DNA deposition and transfer, mostly under tightly controlled conditions. We add to this knowledge pool by investigating the extent to which individuals at Forensic Science SA (FSSA) deposit their DNA on objects throughout the floor of the building where DNA examinations take place. We find that the results obtained in our minimally controlled study allow us to comment on a number of published concepts.